The effect of weight loss on serum ceruloplasmin levels in obese patients - Yigit, Ece; Sayar, Ilknur (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Serum ceruloplasmin level may be a biomarker associated with obesity and cardiovascular risk. We aimed to evaluate the effect of body weight lost by diet and exercise program on metabolic parameters and serum ceruloplasmin levels in obese patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A total of 120 obese patients with BMI ≥30 kg/m2 were enrolled in a 16-week balanced diet program with the goal of losing 10% or more of body weight while maintaining a daily energy deficit of 500-1000 kcal/day. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Mean weights of the patients decreased from 93.2±15.1 kg to 83.2±13.1 kg (p<0.001) and mean BMI decreased from 35.8±5.6 kg/m2 to 31.9±4.9 kg/m2 (p<0.001). Mean ceruloplasmin decreased from 25.2±4.7 mg/dL to 23.6±4.9 mg/dL (p<0.001), mean total cholesterol from 191.8±37.1 mg/dL to 153.8±28.7 mg/dL (p<0.001), mean LDL from 120.3±31.4 mg/dL to 91.1±27.7 mg/dL (p<0.001) and mean fasting blood glucose from 108.2±35 mg/dL to 103.3±81.1 mg/dL (p<0.001). There was a statistically significant and weak correlation between the change in ceruloplasmin and the change in BMI (p=0.016, R=0.233). There was a statistically significant and weak correlation between ceruloplasmin change and weight change (p=0.010, R=0.251). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Obese patients’ serum ceruloplasmin levels were found to decrease with weight loss.